Self-assessed health as a key determinant of lifestyles: An application to tobacco consumption in Argentina - Mariana Conte Grand; Vanesa D'Elia (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2008)
The relationship between lifestyle choices and health has been widely studied in the epidemiological and economic literature. In the last years, empirical research was directed towards the use of recursive systems with structural equations for a health production function and reduced form equations for lifestyles. As a result, behaviors toward health are taken to be determined by exogenous socio-economic variables. In this article, we show that health is a key determinant of health habits. When people feel well, they adopt less healthy behaviors. We use maximum simulated likelihood for a multivariate 5 equation probit model. In that model, lifestyles (diet, exercise, alcohol consumption and smoking) are a function of exogenous socioeconomic variables and self-reported health. Self-reported health varies with socio-economic characteristics and depends on health indicators that are the consequence of lifestyles undertaken in the past (i.e., overweight, blood pressure, diabetes and cholesterol levels). Data is that of adults in Argentina's 2005 Risk Factors National Survey. We find that health partial effects on lifestyle are much larger having accounted for health endogeneity. Accounting for unobservable variables that jointly determine all lifestyles does not change much the magnitude of our results. Our findings are robust to different specifications.
Keywords: I10; I12; 330; lifestyles; health; multivariate probit; smoking; Lifestyle; Gesundheit; Rauchen; Argentinien